Predictive values of risk factors in management of diabetic foot - Al-Obaidi, Safa M.; Tajer, Salah Mahdi; Bakkour, Amine Mohammed (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Outcome of management of patients with diabetic foot is difficult to predict. Assessment of variables in history , examination and investigations were analyzed with outcome of management and whether can be assigned as prognostic factors . Methods: prospective study of 300 patients with diabetic foot in Baghdad teaching hospital during the period from April 2000 to March 2004,certain criteria was taken in history and examination, these were investigated and treated either by conservative procedure or amputation. Results: most common age group was 50-59 years ( 33.3%). The male to female ratio was 2:1. Conservative debridement was performed in ( 60%) of patients while amputation was employed in (40%). amputation was performed in 604 in patient above 60 years and in(75%) of patients who had diabetic foot lesions for > 2 weeks,and in 90% of smokers for 10 years or more. Amputation was needed in (71%) in those who had history of previous ulceration and 72.5% of patients who had positive history of previous amputation. Amputation was needed in (88%) of those who had their temperature >38°C. in (91%) of patients who had diabetic foot lesion of Wagner grade>III and 91%. patients with X-ray findings of osteomyelitis. Conclusions: Highly significant association was found between amputation with following variable , smokers > 10 years, patients with a temperature of > 38°C, Hypertension > 140/90 mmHg Wagner grade > III, white blood cell count of > 20,000/cc and positive foot X-ray findings. Slight significant association of amputation and the following variables: Age >60 years, duration of foot lesion >2 weeks, history of previous amputation, previous ulceration, negative pedal pulses, deformed feet and patients who had impaired normal vision.